2013
DOI: 10.1038/srep01375
|View full text |Cite
|
Sign up to set email alerts
|

When do negative and positive emotions modulate working memory performance?

Abstract: The present study investigated when emotion modulates working memory from the perspective of neural activation. Using fMRI, we measured brain activity during the encoding and retrieval phases of a reading span test (RST) that used emotional contexts. The emotional RST required participants to read sentences that elicited negative, neural or positive emotional states while they were memorizing target words from the sentences. Compared with the neutral RST, the negative RST activated the right amygdala during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 38 publications
1
23
1
4
Order By: Relevance
“…First, the sample was modest in size and In spite of these limitations, data highlight an activation pattern within frontoparietal and occipital regions during encoding that underlie interference control during a WMC task. The modified Rspan task appears to provide a tool for probing neural circuitry of WMC that differentiates the regions involved in interference control from set size, which may be relevant in future studies assessing populations (e.g., posttraumatic stress disorder; Bomyea, Amir, & Lang, 2012) or affective states (e.g., emotional arousal; Osaka, Yaoi, Minamoto, & Osaka, 2013) marked by deficits in this ability. In addition, empirical interest in training of cognitive functions dependent on interference control and working memory capacity in healthy and clinical samples has recently grown (Bomyea et al, 2015), with evidence that training-related changes may occur in both structural and functional neural activity (Engvig et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…First, the sample was modest in size and In spite of these limitations, data highlight an activation pattern within frontoparietal and occipital regions during encoding that underlie interference control during a WMC task. The modified Rspan task appears to provide a tool for probing neural circuitry of WMC that differentiates the regions involved in interference control from set size, which may be relevant in future studies assessing populations (e.g., posttraumatic stress disorder; Bomyea, Amir, & Lang, 2012) or affective states (e.g., emotional arousal; Osaka, Yaoi, Minamoto, & Osaka, 2013) marked by deficits in this ability. In addition, empirical interest in training of cognitive functions dependent on interference control and working memory capacity in healthy and clinical samples has recently grown (Bomyea et al, 2015), with evidence that training-related changes may occur in both structural and functional neural activity (Engvig et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Ainda relacionado aos estudos que investigaram o desempenho verbal da MO, Osaka et al (2013) demonstraram piores resultados para o desempenho verbal da MO (Reading Span) com estímulos negativos em comparação com estímulos neutros. Além disso, Fairfield et al (2014) observaram que a precisão com palavras positivas e negativas diminuiu conforme as listas se estenderam, embora a extensão da lista não tenha tido impacto na recordação de palavras neutras.…”
Section: A Influência Dos Estímulos Emocionais Em Tarefas De Mo Verbaunclassified
“…It has been reported that both positive and negative affective picture stimuli improve working memory performance (Levens & Phelps, 2008;Lindström & Bohlin, 2011). Other studies have found that while positive stimuli are beneficial for working memory performance, negative stimuli impair it (Osaka, Yaoi, Minamoto, & Osaka, 2013;Perlstein, Elbert, & Stenger, 2002). A reason for the diverging results might be that when stimuli are perceived as threatening, the attentional resources are directed towards the threat, disrupting working memory performance (Pessoa, 2009).…”
Section: Introductionmentioning
confidence: 99%